Analysis of nitrogen adsorption capability at various activation temperatures of Klaten natural zeolite - Caroko, Novi; Sukamta, Sukamta (Politeknik Negeri Lhokseumawe, 2024)
The Pressure Swing Adsorption (PSA) method operates by passing air through an adsorbent to produce concentrated oxygen gas. Zeolites are commonly utilized as adsorbents due to their ability to adsorb nitrogen from the surrounding air. Two types of zeolites commonly employed are natural and synthetic zeolites. While the utilization of natural zeolites as adsorbents in oxygen purification remains limited, their potential as an alternative adsorbent is worth exploring in this field. This study focused on developing physically activated Klaten natural zeolite as an adsorbent to enhance oxygen purity. Physical activation involved heating for 1.5 hours using an electric oven at four temperature variations (250ºC, 300ºC, 350ºC, and 400ºC). Additionally, four distinct flow rates were tested: 0.1; 0.5; 1.0; and 1.5 lpm. Oxygen purification testing revealed that higher activation temperatures led to greater increases in oxygen concentration. The highest increase of 2.45% was achieved at an activation temperature of 400ºC, while the lowest increase of 1.75% was observed at 250ºC with a flow rate of 0.1 lpm. With a 10-minute holding period, oxygen content during the adsorption process ranged from 1.35% to 2.45%, compared to 0.60%-0.75% without holding. Physical activation of zeolite from Klaten enhanced its nitrogen absorption capacity, indicating the potential of natural zeolite from Klaten for oxygen purification through optimized activation processes, possibly via chemical activation